2006
DOI: 10.1002/ppul.20510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different ventilation modes with FC‐77 on pulmonary inflammatory reaction in piglets after cardiopulmonary bypass

Abstract: Both TLV and PLV improved oxygenation and reduced pulmonary inflammatory reaction in piglets after CPB, whereas TLV is more effective than PLV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…By contrast, studies in different lung-injury models generally showed a decrease in expression of several cytokines, such as IL-1β [23,25,27], IL-6 [27,71,73,74] and IL-8 [23,27,28,73,[85][86][87], in the PLVtreatment group compared with the respective GV-treatment group. By contrast, the effect of PLV with a PFC on TNF-α levels did not follow a consistent trend in the various animal studies [71,83,[88][89][90][91] and may depend on where TNF-α levels were assessed.…”
Section: Review Lehmlermentioning
confidence: 89%
See 3 more Smart Citations
“…By contrast, studies in different lung-injury models generally showed a decrease in expression of several cytokines, such as IL-1β [23,25,27], IL-6 [27,71,73,74] and IL-8 [23,27,28,73,[85][86][87], in the PLVtreatment group compared with the respective GV-treatment group. By contrast, the effect of PLV with a PFC on TNF-α levels did not follow a consistent trend in the various animal studies [71,83,[88][89][90][91] and may depend on where TNF-α levels were assessed.…”
Section: Review Lehmlermentioning
confidence: 89%
“…A recent study demonstrated that TLV can be more effective at reducing pulmonary neutrophil infiltration than PLV [73]. Even systemic administration of PFCs, such as FC-77 administered intraperitoneally 48 h prior to lung injury, could decrease neutrophil infiltration in the lung [77].…”
Section: Anti-inflammatory Effects Of Pfcsmentioning
confidence: 97%
See 2 more Smart Citations
“…Beside positive effects on gas exchange, lung mechanics, and ventilation/perfusion matching, animals treated with liquid ventilation also exhibited attenuated pulmonary damage with concomitant reduction in pulmonary neutrophil sequestration (19,21,32,39). A clinical trial investigating PFC treatment in trauma patients with acute lung injury demonstrated reduced neutrophil counts and decreased levels of proinflammatory cytokines in bronchoalveolar lavage fluid (7).…”
mentioning
confidence: 99%